Performance comparison of series and parallel damped LCL filters using 5-level voltage source converter - Shanono, Ibrahim Haruna; Nor Rul Hasma, Abdullah; Hamdan, Daniyal; Aisha, Muhammad (Springer Nature, 2020)
The high harmonic content produced by conventional converters has resulted in the increased system size and cost, due to the need for large-sized low-order harmonic passive filters and cooling system requirement. Given that, multilevel inverters and special modulation techniques were developed to suppress or eliminate the low-frequency harmonics and the left behind high-order ones are eliminated using a high-frequency small-sized filter. Hence, this paper designs and compares the total harmonic distortion (THD) and efficiency values of three set of filters, namely LCL filter, LCL with series and parallel resistance on a novel five-level multilevel voltage source inverter topology. The novelty lies with the proposed inverter, which, apart from using a single direct current source, it can extend it elimination capability beyond the normal five level using the concept of multiple switching per step and an optimised selective harmonic elimination pulse width modulation. The converter can eliminate eleven lower-order odd nontriplen harmonics, hence making the 37th harmonic at 1.85 kHz to be the first dominant harmonic. At 2-kW loading, two of the filters have THD below 5%, therefore satisfying the IEEE 519 standard. The parallel resistance damped filter (LCL-P-R) has less THD value but poor efficiency due to the resistance introduced into the circuit. The study was carried out using PSIM and MATLAB software.